Diagnostic Utility of FAS Sequencing in Suspected ALPS: Insights from a Large Clinical Cohort - Wenying Zhang; Jack Bleesing (Journal of Clinical Immunology, 2026)
Abstract Autoimmune lymphoproliferative syndrome (ALPS) is a rare immune dysregulation disorder most commonly caused by defects in the FAS-mediated apoptosis pathway. While germline FAS variants account for the majority of cases, somatic variants, typically restricted to double-negative T cells (DNTCs), may be under-detected in routine testing. We retrospectively analyzed FAS full-gene sequencing in 686 probands and 3 family members with suspected ALPS to assess diagnostic yield, variant spectrum, and clinical utility. Germline FAS variants were identified in 73/685 probands (10.7%) using whole blood or cytobrush samples. Somatic FAS variants were detected in 8/22 cases (36.4%) using sorted DNTCs, demonstrating a substantially higher diagnostic yield in patients with strong clinical suspicion but negative germline testing. A total of 65 unique diagnostic sequencing variants were identified, of which 49% were previously unreported. Variants were enriched in the intracellular domain (65%), with most disrupting the death domain. Three cases with copy number variants (CNVs) were identified, including deletions spanning intron 5 to exon 9, intron 6 to exon 9, and a partial exon 9 deletion involving the C-terminal region of FAS , expanding the known spectrum of structural variants. One case demonstrated a somatic FAS variant with a markedly higher level than wild-type allele in DNTCs, consistent with somatic loss of heterozygosity (sLOH), representing the second reported case of ALPS-sFAS/sLOH. These findings highlight the importance of comprehensive FAS testing, including germline and somatic analysis with DNTC-based sequencing and CNV detection, to improve diagnostic accuracy and inform clinical management in suspected ALPS.